Firm Fundamentals and Cost of Capital of Non-financial Firms in Nepal - Lamichhane, Pitambar (Management Dynamics, 2021)
This paper examines the impact of firm fundamentals on the cost of capital (COC) of non-financial firms in Nepal for the period 2004/05-2017/18. This study has applied a causal-comparative research design to investigate the effect of firm fundamentals on COC. COC is the weighted average cost of capital of debt and share capital and is used as a dependent variable and bank-related fundamental variables such as growth rate of net sales, growth rate of assets, leverage ratio as debt to capital, dividend payout ratio, earning variability, assets tangibility and liquidity ratio are explanatory variables of this study. Estimated results show that liquidity, earnings variability, dividend payout and leverage ratio are key factors influencing COC in Nepalese non-financial firms. The estimated regression results of this paper reveal that COC is positively affected by dividend payout and inversely influenced by leverage, earning variability, and liquidity. This paper concludes that Nepalese non-financial firms with less dividend distribution using high financial leverage with a strong liquidity position and higher-earning variability can minimize the cost of capital. Nepalese firms should pay more dividends to use cheaper sources of debt and increase liquidity position and financial leverage to minimize the average cost of capital. Policymakers can use the results of this study to formulate and implement policies about firm fundamentals, cost of capital and business activities.